Impact of Prior Chronic Kidney Disease and Newly Detected eGFR Impairment at Admission on Outcomes and Prognosis of Hospitalized COVID-19 Patients – A Single-Center Cohort Study - Kania M; Terlecki M; Batko K; Rajzer M; Malecki MT; Krzanowski M (International Journal of General Medicine, 2025)
Michał Kania,1,2 Michał Terlecki,2,3 Krzysztof Batko,2 Marek Rajzer,2,3 Maciej T Malecki,1,2 Marcin Krzanowski2,4 1Department of Metabolic Diseases, Jagiellonian University Medical College, Krakow, Poland; 2University Hospital, Krakow, Poland; 3Department of Cardiology, Interventional Electrocardiology and Arterial Hypertension, Jagiellonian University Medical College, Krakow, Poland; 4Department of Nephrology and Transplantology, Jagiellonian University Medical College, Krakow, PolandCorrespondence: Marcin Krzanowski, Jagiellonian University Medical College, Department of Nephrology, 2 Jakubowskiego Str, 30-688, Krakow, Poland, Email marcin.krzanowski@uj.edu.plBackground and Hypothesis: Chronic kidney disease (CKD) is a major prognostic factor in COVID-19. Little is known about the significance of newly detected renal impairment (RI) for COVID-19 patient outcomes. This study assessed the effect of prior CKD and RI at admission on in-hospital mortality in COVID-19 patients.Methods: A total of 5191 consecutive patients with COVID-19 admitted between March 6, 2020 and May 31, 2021, to the University Hospital in Krakow were analyzed. The main outcome was in-hospital death from any cause compared between the three study groups – patients with a prior history of CKD (group A), no history of CKD and eGFR on admission < 60 mL/min/1,73 m2 (group B), and no history of CKD and eGFR on admission > 60 mL/min/1,73 m2 (group C).Results: Of 5191 patients, 2348 (45.2%) were women and 2409 (46.4%) were older than 65 years (mean age of 61.98± 16.66 years). There were 483 (9.3%) patients in group A, 1009 (22.2%) in group B and 3699 (68.5%) in group C. Groups A and B were older and had higher cardiometabolic burden compared to group C. Multivariable logistic regression showed that older age, higher CRP, WBC, D-dimer levels, HF, and being in groups A or B were associated with higher in-hospital mortality. Group B had the highest risk (OR 3.003, CI 2.298– 3.926) compared to group A (OR 2.020, CI 1.636– 2.494) and group C (reference).Conclusion: COVID-19 patients with prior CKD and newly detected RI have higher odds of in-hospital death compared to those with normal kidney function. Special attention is needed for newly detected RI cases in COVID-19 patients.Keywords: kidney disease, mortality, risk factors, COVID-19, chronic kidney disease, acute kidney injury, SARS-Cov-2